The application of corporate governance to the earnings management of the banking industry in Indonesia in the 2007-2009 period - Bimantoro Adi Pratomo (Institute of Accounting Research and Novation (IARN), 2021)
The aims of this research is to examine the influence of corporate governance mechanisms, such as, board of commissioner composition and size, audit committee size, composition of independent audit committee members and their expertise on the earnings management practice in public bank companies listed in Indonesia Stock Exchange. The samples of this research is all of public banks companies existed in Indonesia in the year of 2007-2009 which were listed in Indonesia Stock Exchange. The research data were collected from public bank’s financial statement and annual report for the period of 2007 until 2009. From purposive sampling method, I have collected 72 observations from 24 public banks companies/3 years. By using multiple regression analysis as the research method, the results shown that five independent variables influenced earnings management of public banks companies simultaneously. The conclusion of this research is only board of commissioner composition and audit committee expertise that significantly affect earnings management, while board commissioner size, composition of independent audit committee members and size have no significant effect to earnings management